Osteology, natural history notes, and phylogenetic relationships of the poorly known Caribbean frog Leptodactylus nesiotus (Anura, Leptodactylidae) - Ponssa, María Laura (2010)
The Leptodactylus melanonotus group consists of 15 species, but references to skeletal characters are available for only three species: L. leptodactyloides, L. melanonotus, and L. diedrus. Leptodactylus nesiotus is a member of the melanonotus group known only from the type locality, Bonasse swamp, on the Southwestern peninsula of Trinidad, Trinidad and Tobago. This species has been categorized as vulnerable given its restricted distribution. Herein, we report the adult osteology of L. nesiotus, the skeletal characters are compared with the available data from other Leptodactylusspecies. A phylogenetic analysis recovers a paraphyletic L. melanonotus group relative to the L. latrans group. A monophyletic “latrans-melanonotus” clade is supported by five synapomorphies. L. nesiotus is recovered as the sister species of L. validus, a relationship supported by two synapomorphies: T-shaped terminal phalanges and a dark-colored stripe on the outer surface of arm. In addition, we report on the ecology of this poorly known species.